Efforts Of School Heads In Improving Teacher Performance - Imam Tabroni; Adinda; Isty; Syifa (Kampret Journal, 2023)
This study aims to determine the principal's efforts in improving teacher performance at SMPN 3 Pasawahan, Purwakarta Regency, in this study will explore the problems in the inhibiting and supporting factors in improving teacher performance. The method that the researcher uses is a qualitative descriptive approach, in which in this study data will be collected according to the events that occurred or the facts of actual events. The goal is that real data can be found directly with actual conditions. The results obtained from this study have shown that the principal of teachers at SMPN 3 Pasawahan Purwakarta has made several efforts to improve the performance of teachers with the aim of achieving these efforts successfully. These efforts are such as conducting Work Program Meetings in Schools, Providing Motivation and Support for Educators or Teachers, Providing Guidance and Guidance for Educators or Teachers, Conducting Observations in the School Environment. However, there are also inhibiting factors for the principal in improving the performance of teachers at SMPN 3 Pasawahan Purwakarta, one of which is that most teachers have not had time to become PNS 30% so 70% of them are honorary teachers. Therefore, because honorariums are not synonymous here, because there are also those who teach, others like to be constrained when there are activities at school, it is related to honorary teachers who teach in two places. Finally due to a shortage of personnel. That is one of the inhibiting factors but can be overcome by time collaboration work, even if there is no one, the existing teacher will replace it so that the process goes on as usual.